Strategi Pemerintah Desa Dukuh dalam Mengoptimalkan Potensi Ekonomi Pariwisata - Putra Pratama, Febian Autentika May (Jurnal Kajian Ruang, 2024)
Dukuh Village is in Banyudono District, Boyolali Regency, Central Java, Indonesia. Dukuh Village has a lot of tourism potential that can be increased to advance it. Currently, Dukuh Village has many tourist attractions, such as Umbul Peceren, Pengging Square, Ki Ageng Handayaningrat Grave Park Religious Tourism, and Bird Market. These tours are supervised by Village-Owned Enterprises (Bumdes). This agency was formed by village officials in 2019 to manage tourism potential in Dukuh Village. However, even though the Dukuh Village tourism sector is developing rapidly, there is still a lot of development that needs to be done so that PAD becomes better and contributes to the Boyolali Region. This research aims to see how the Dukuh Village government uses various approaches to increase local revenue and introduce tourism networks to the general public. This research was prepared through interviews, qualitative descriptive methods. The research results show that there are several strategies that can be used. One way is to start marketing and promotional efforts to increase the number of visitors who come to Dukuh Village. This research also focuses on developing and optimizing Dukuh Village tourism